DENTAL DISEASES AND INFORMATION ABOUT THEM - Shukurov Sherzod Shukhratovich; Saidmurodov Dilshod Kamolovich; Jumaev Gofur Ziyodovich (Journals Park Publishing, 2022)
In the matrix of identical mitochondria, a cascade and pyruvatdegenase reaction of the aerobic oxidation of glucose in the tricarbonate acid cycle occurs, as a result of which, in the respiratory chain of mitochondria, which are localized in the internal mitochondrial membrane and are directly responsible for the synthesis of adenosintrifosphate (ATF), the main energy source of all processes occurring in the cell, oxidized substrates are formed.
Keywords: chain; mitochondria; death